An analysis of Loan Loss Provisioning (LLP) behavior in Indonesian Banking from 2011 to 2016 - Wu, Zihang (2017)
This paper studies the Loan Loss Provisioning behavior by banks in Indonesian for the period 2011 through 2000. We test the X-efficiencies, Z-score, Macroeconomic Variable, Income smoothing and Capital management hypothesis. This study concludes that LLP is influenced by more than one factor. There is a significant positive relationship between X-efficiencies and LLP, Z-score has a significant negative related with LLP, Macroeconomic variables only unemployment rate significantly negative associated with LLP. There is a countercyclical of loan loss provisions in Indonesian banks. Besides that, we find management of banks adopt income smoothing to manipulate their earning in Indonesian banks. Also, the management of banks with higher capital use capital ratio to boost their capital.